PENERAPAN MODEL PEMBELAJARAN TIME TOKEN UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V PADA MATA PELAJARAN PAI DAN BUDI PEKERTI SDN 006 PANGKALAN INDARUNG KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI - Wirda Yanti; Ikrima Mailani; A Mualif (Universitas Islam Kuantan Singingi, 2022)
The problem of this research begins with the learning outcomes of fifth grade students in the subjects of Islamic Religious Education and Morals at SD Negeri 006 Pangkalan Indarung which is still relatively low, as evidenced by the existence of student scores below the KKM. This is the background for researchers to conduct research using the Time Token learning model, the Time Token model is a learning model with the characteristics of a time mark or time limit. This learning model is suitable for developing students' social skills or avoiding students dominating speech and other students just being silent. The purpose of this study was to determine the application of the Time Token learning model to improve student learning outcomes, as well as the obstacles faced by students during learning. The type of research used is Classroom Action Research (CAR), the subject of this research is the fifth grade students of SD Negeri 006 Pangkalan Indarung with a total of 29 students, data collection techniques used are observation, interviews, test techniques and documentation. by using the Time Token learning model can improve student learning outcomes, this is evident from the observations obtained in each cycle, Pre-Cycle 31.03%, Cycle I percentage is 44.82% Cycle II percentage is 62.06% and Cycle III percentage is 86.20 %. So it can be concluded that the application of the Time Token learning model can improve the learning outcomes of fifth grade students at SD Negeri 006 Pangkalan Indarung.